SISTEM PENYELENGARAAN ORGANISASI NEGARA - Sahputra, Adi; Devra, Desi Devrika (Komunitas Manajemen Kompetitif, 2025)
Given the failure of the existing complaint system, has established a new institution to cover the weaknesses of the existing regulatory body. This new institution relies on the year by the Presidential Secretary in 2000, with the exception of problems, except for problems. and Social Impedi Ments. This article examines these problems and proposes some reforms. During this ongoing reform period, the government still leaves various problems. In particular, those associated with efforts to improve the quality of good and clean governance, far from expectations. Keywords:System,Implementation,Organization,State.